Role of Dexmedetomidine in Attenuation of Hemodynamic Response to Laryngoscopy - A Dose-Finding Study - Abbas SM, Siddique M, Abbas MQ, Farooq MF, Malik S, Khan HA (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: Determining efficacy of pre-operative bolus dose of dexmedetomidine 0.75 and 0.5µg/kg as an infusion and compare it with placebo in attenuation of hemodynamic response to laryngoscopy and tracheal intubation (LTI). Design: Double-blind randomized control. Place & duration: Sindh Institute of Urology & Transplantation, Karachi, Pakistan, from August 2019 to August 2021. Methodology: Patients were stratified into three groups. Group A received normal saline (NS), Group B received dexmedetomidine 0.5 μ/kg and Group C received dexmedetomidine 0.75 μ/kg as an infusion over 10 minutes followed by standardized general anaesthesia. Primary outcome measures were hemodynamic variables at 1, 3, 5 and 10 minutes post LTI. Secondary outcome measures were adverse effects related to dexmedetomidine. Results: Both dexmedetomidine groups showed better attenuation of hemodynamic response to LTI thansaline group. Dexmedetomidine 0.75 µg/kg attenuated hemodynamic response to LTIsignificantly better thandexmedetomidine 0.5 μ/kgand placebo without causing any statistically significant adverse effects. Practical implication: The function of dexmedetomidine in attenuating hemodynamic response to laryngoscopy has several practical implications, including improved patient safety, optimal dosing, reduced anaesthetic requirements, cost-effective treatment, and enhanced patient comfort. Conclusion: Dexmedetomidine 0.75 µg/kg efficient than 0.5 µg/kg and placebo in attenuating hemodynamic response to LTI when given as a pre-induction bolus. Keywords: Anesthesia; Dexmedetomidine, Laryngoscopy, Intubation, Stress Response.